Intelligent transport systems for South Africa: contextual investigation of the application of non-motorised transport intelligent transport measures - Haider, Mehdi (Department of Civil Engineering, 2025)
The transition towards "smart" environments utilising technology has given rise to Intelligent Transport Systems (ITS) to enhance transport system efficiency and safety. Often overlooked Non-Motorised Transport (NMT) has not received sufficient attention, despite its importance in making cities sustainable. The development of ITS has been focused on motorised vehicles, with little attention paid to NMT. This study aims to bridge the gap where it will investigate different advancements in ITS specifically targeted towards NMT and analyse their applicability in South Africa, using a few case studies within the City of Cape Town. The objective is to evaluate the effectiveness of such measures and provide recommendations for further testing or implementation of identified measures. This dissertation examines the impact, types, and advantages of Intelligent Transport System (ITS) measures, focusing on Non-Motorised Transport (NMT), and identifies significant applicable lessons for specific contexts. Several studies suggest that the ITS measures have multiple benefits, including reducing traffic congestion, improving road safety, lowering fuel consumption, and enhancing public transport reliability. Vanderschuren (2006) identified six key objectives of ITS measures: safety, mobility, efficiency, productivity, sustainability, and environmental impact. This dissertation explores some of the ITS measures and how they intend on achieving their objectives. This dissertation focuses on exploring the benefits of a few established Intelligent Transportation Systems (ITS) measures globally and identifying key improvements and benefits. The purpose of studying the literature is to determine the success of implementing these ITS measures internationally and the benefits yielded. This study presents three international case studies and results. The first study conducted by the United States of America's Department of Transportation Federal Highway Administration where they evaluated the safety effectiveness of Pedestrian Countdown Signals (PCSs) in Charlotte (North Carolina), and Philadelphia (Pennsylvania). The study results showed that after the implementation of PCSs, pedestrian crashes decreased by 9%, total crashes decreased by 8%, and rear end crashes decreased by 12%. The second case study conducted in Rome, Italy, evaluated the safety improvements obtained with a LED lighting system positioned at the crosswalk section. The study showed that the LED lighting system reduced cars' mean speed by 19.3% at the crosswalk section in illuminated conditions and even by 16.4% in the absence of pedestrians. The third case study from Haarlemmermeer, Netherlands, discussed the use of thermal detection sensors to improve the efficiency of pedestrian push buttons at signalised intersections for smoother traffic, less vehicle idling, and fewer frustrated motorists. By implementing these sensors, the city officials reduced vehicle idling time, air pollution and interruptions in vehicle flow caused by jaywalkers and needless pedestrian green calls. The dissertation concludes that studying the benefits and effectiveness of NMT based ITS measures can provide greater insight into pedestrian safety and can help decide which interventions could work in a local contexts. This dissertation discusses the challenges facing NMT, such as walking and cycling in African cities. Despite the fact that walking is the dominant mode of transport in African cities, neither walking nor cycling has received the attention they deserve in terms of policy development and implementation. The legacy of colonialism and contemporary focus on automobile-dependent planning are cited as reasons for the lack of attention given to NMT (Vanderschuren and Galaria, 2003). South Africa's complex history, including apartheid, has resulted in unsustainable urban areas with a lack of accessibility. The end of apartheid has led to freedom of movement but has also resulted in an increased demand for transport. Majority of South African commuters are required to travel long distances for job opportunities. Commuters use public transport as long travel distances make walking or cycling infeasible modes. To address this problem, South African cities are adopting a "Corridor City" with Transit Orientated Development, where nodes across the urban area are identified for densification with mixed-use developments and corridors linking them through strong public transport corridors. This strategy will reduce travel time to job opportunities making NMT a more feasible mode of transport. If this proves successful demand for NMT will significantly, increase thus will require to carefully planning infrastructure to accommodate future demand. The dissertation explored various ITS measures for NMT globally, but local contextual constraints may affect their effectiveness. Further, in dissertation it explains how non-compliant pedestrian behaviour in South Africa presents a challenge for the ITS measures that rely on traffic rules compliance. This also highlights the different groups of ITS measures and their applicability in the South African context. This dissertation explored two local case studies in Cape Town namely a combination of a traffic signal countdown timer and LED lane lights and the second case study of thermal sensors installed at a pedestrian crossing. Based on this dataset it appears that compliance have not improved by implementation of traffic signal countdown timer, hence, in this case study the countdown pedestrian signal appears to be ineffective in influencing pedestrian behaviour. To determine how effective the implementation of the LED lane lights are a comparison between the numbers of drivers adhering to the solid-white stop line (during the vehicle-red signal phase) pre-and post lane lights were installed. It is evident from the case study that there is a clear reduction (from 26% to 6%) in the average number of stop line violations, specifically on weekends. Due to the fact that driver behaviour during the week is expected to be relatively more aggressive compared to weekends the data reflected higher violations than in comparison to weekdays. The next case study explored was recent implementation of pedestrian thermal sensors installed in the City of Cape Town as a pilot project. The thermal sensor since installation resulted in no more cases of signal vandalism reported and it appears that pedestrian crossing efficiency has been improved. Unfortunately, limited data pre-installation was available hence; all analysis done was post installation in comparison to design norms. Early indications shows a 40% improvement however longer trails are required to be tested for conclusive evidence. In summary, the literature and case studies support the idea that ITS measures that requires high levels of traffic compliance are likely to be ineffective in the South African context but ITS measures that do not require high levels of traffic compliance is applicable to South African context. The challenge is prioritisation and lack of infrastructure, as road safety is such a prominent problem in South Africa funding and focus are geared towards making road environments safe before funding is spent in optimisation. The secondary challenge is that the NMT network within South Africa is not at the level of developed counties thus before implementation of ITS measures for optimisation NMT infrastructure networks required to fully established.